The fortunes of everyman in twentieth-century German drama war, death, morality - Murdoch, Brian 1944- (Camden House, 2022)
Death still comes to everyman, but this study of three twentieth-century German plays shows the harder challenge of living without salvation in an age of war and unprecedented mass destruction